Improving provider, patient and health systems outcomes: a qualitative analysis of Project ECHO. (20th October 2021) - Jenkins, C; Diffin, J; McTernaghan, T; Watson, M
Abstract: Background: Project ECHO (Extension for Community Healthcare Outcomes) is an internationally recognised tele-mentoring intervention that has been implemented in over 40 countries. The model connects specialist healthcare providers (hubs) with providers in primary and community practice (spokes), often in rural and isolated areas. Objectives: Project ECHO aims to improve healthcare provider's skills, confidence and knowledge, and to create a community of practitioners using the hub and spoke model. Analysing interview data from 27 Project ECHO network leads and participants in Northern Ireland, this study sought to assess the impact of Project ECHO on improving provider, patient and health system outcomes. Results: Having access to a specialist, a space to share experiences, and being able to disseminate up-to-date best practice were all cited as improving provider knowledge. Providers described improved outcomes for patients such as receiving a new treatment or an efficient referral. Providers reported being more confident in managing patients and thus were less likely to refer unnecessarily, and links between providers at primary and secondary levels being improved. ECHO was deemed an acceptable methodology in terms of format and in improving access to education and training by removing geographic barriers and reducing time barriers. Conclusions: This is one of the first studies to qualitatively analyse outcomes across a number of different ECHO networks, and involving both health and social care networks. The results indicate the benefit of ECHO in improving provider, patient and healthcare outcomes. This has implications for future resourcing decisions, particularly within the context of COVID-19 in which virtual and online training is necessitated by social distancing requirements. This study has implications for wider international contexts in which ECHO may be piloted to address similar challenges. Key messages: Participants across our study described Project ECHO as having a positive impact on provider, patient and health systems outcomes. Project ECHO was described as an acceptable approach to training and education that improved access through removing geographic barriers.